Strategi Pemasaran Ayam Ras Pedaging (Broiler) - Saroba, Apni (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Business activity simply can not be separated from marketing activities. The importance of marketing cause businesses strive to achieve success is by doing various steps of marketing strategies. The purpose of this study to determine the marketing strategy used in the business of broiler (broilers) in District Rambah Rokan Hulu Regency. Techniques of data collection using surveys and interviews. Data analysis technique used is SWOT analysis. Results of the study, the total score of the IFE Matrix is of 3.23 and the EFE Matrix has a total score of 3.05. In the IE Matrix broiler business (broiler) in the position I that grow and establish who has the opportunity and strength. Strategies that can be used is the strategy of vertical integration (Vertical Integration). Priority strategies that can be implemented based on the analysis QSPM are entrepreneurs take advantage of strategic business location for developing the existing business in order to meet the high market demand with a value TAS (Total Atractive Score) of 7.26.Â Keywords: Internar External factors, SWOT, QSPM